2017
DOI: 10.1007/s11999-016-5091-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonmodular Tapered Fluted Titanium Stems Osseointegrate Reliably at Short Term in Revision THAs

Abstract: Background The ideal femoral component for revision THA is undecided. Cylindrical nonmodular stems have been associated with stress shielding, whereas junctional fractures have been reported with tapered fluted modular titanium stems. We have used a tapered fluted nonmodular titanium femoral component (Wagner Self-locking [SL] femoral stem) to mitigate this risk. This component has been used extensively in Europe by its designer surgeons, but to our knowledge, it has not been studied in North America. Added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Additionally, previous work has shown good outcomes in complex cases using monoblock stems. [21][22][23][24] Regardless of implant type, precautions must be taken to limit intraoperative fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous work has shown good outcomes in complex cases using monoblock stems. [21][22][23][24] Regardless of implant type, precautions must be taken to limit intraoperative fractures.…”
Section: Discussionmentioning
confidence: 99%
“…It can also promote bone in-growth to achieve biological xation with the metaphysis and diaphysis. Sandiford et al [24] reported 104 femoral revisions using the Wagner SL stem, with a follow-up of 24 -46 months, and found that no femoral stems had failed from aseptic loosening. Only one patient with infection of the stem and cup required operation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Sandiford et al [24] reported 104 femoral revisions using the Wagner SL stem, with a follow-up of 24 -46 months, and found that no femoral stems had failed from aseptic loosening. Only one patient with infection of the stem and cup required operation [24]. Previous studies have shown that the Wagner tapered femoral stems have excellent survival rates and favorable results in revision and primary THA [25,26], potentially making it a better choice.…”
Section: Discussionmentioning
confidence: 99%
“…Sandiford 21 followed up 104 patients who underwent Wagner SL femoral stem revision for 2 years. The bone remodeling rate was 47%.…”
Section: Discussionmentioning
confidence: 99%